Recent Advances in Nano Silver Catalysis for Organic Transformations - Du, Yuxuan (Transactions on Materials, Biotechnology and Life Sciences, 2024)
This account explains three types of reactions to form homogeneous or heterogeneous nanocatalysts; coupling reaction, reduction reaction, and cascade reaction. Catalyst is an important technology and has various advantages. Metal oxides, or metals, placed on a support or carrier in a different state, are the catalytically active part of a solid catalyst. Particles that range in size from 1 to 100 nm are referred to as metal nanoparticles, and they are frequently used in synthetic organic chemistry. Based on their characteristics, nanocatalysts have several benefits, including increased chemical reaction selectivity and efficiency. Furthermore, this report shows different example that scientists exploring nanocatalysts through coupling reactions, reduction reactions, and cascade reactions, and different ways, such as experiments or filter paper to produce catalysts. Discovering that nanocatalysts not only have the function of accelerating but also help the treatment of tumors. In the future, nanocatalysts will find more applications in other industries. It will enable people to succeed more highly in a variety of industries.